HUBUNGAN PERAWATAN DAN WAKTU PEMAKAIAN LENSA KONTAK LUNAK TERHADAP IRITASI PADA MATA - Putra, M Fahruddin Alyahya; Muftia, M (JURNAL KESEHATAN TERAPAN, 2021)
Background: The use of contact lenses causes many negative impacts that need to be watched out for for users, especially if they do not follow the usage rules. Methods: This analytical survey research with a cross sectional approach was conducted in 2019 with a minimum sample size of 52 people using a simple random sampling technique. Data obtained through interviews using a questionnaire and analyzed univariate and bivariate using SPSS ver 25.0. Results: There was a significant relationship between treatment and duration of wearing contact lenses with eye irritation (p value = 0.008). Conclusion: There is treatment and duration of wearing contact lenses with eye irritation can be used as input to develop health services. Keywords: Eye Irritation, Long Use of Contact Lenses, Treatment